The quality of locally produced synthetic resin teeth a preliminary study - Largoza, Ma. Nyra T. (The Journal of the Philippine Dental Association)
There is still no recognized body which conducts tests to verfy the quality of locally manufactured acrylic resin teeth. In this study, three different brands were tested. Four sets of upper anterior teeth of four different shades for each brand were subjected to the following: Blanching and Distortion Test, Craze Resistance Test and Color Stability Test. One foreign, A.D.A. approved brand is included in the testing as a basis of comparison. One half of the sample set were exposed, their contralaterals acted as controls. Results showed that all three local brands passed all three tests.